MSMEs Empowerment Communication in New Normal Era: The Case of Mini University Kaltim Preneurs in East Kalimantan, Indonesia - Rina Juwita; Annisa Wahyuni Arsyad; Johantan Alfando (Budapest International Research and Critics University, 2020)
Indonesia’s economy consists mainly of micro, small and medium enterprises (MSMEs). In this pandemic situation, the government through its various institutions has made various efforts to save Micro, Small and Medium Enterprises (MSMEs) from the impact of covid-19, including Indonesian Central Bank located in East Kalimantan Province. Its existing empowerment program named Mini University Kaltim Preneurs made an innovation to accommodate all its graduates to support each other in a local market place named Minishop. This study try to analyse the empowerment communication strategy implemented by Bank Indonesia-East Kalimantan Area in strengthening the local MSMEs in new normal era, and map out the barriers and challenges faced to improve the program. This research employs qualitative method, and using empowerment communication theory as an umbrella to analyse the data. The study found that the success of MSME rescue policy from the impact of the COVID-19 pandemic needs to be supported by some specific strategies to maintain the sustainability of MSMEs as one of the players of the Indonesian economy.